The Obsession with Measurement and Construction of Possible Futures in Education - Massimiliano Tarozzi (University of Bologna, 2023)
Over the last decade, there has been a growing consensus, including in Italy, that it makes sense to provide an objectively measurable empirical basis for educational policies and practices in order to escape from the uncertainty of practices based on individual experience or subjective values. The quantification of the social sphere, the "metric society" (Mau, 2019), and data-driven models of governance have led not only to "learnification", a culture of performativity and standardised testing as the dominant model (Biesta, 2010), but also to a loss of future-oriented visions as these latter are overwhelmed by statistical models of anticipation. The main aim of this paper is to critique the post-positivist epistemological assumptions of so-called Evidence Based Education as well as the neoliberal organisational models whose indiscriminate application to professionals in education robs these roles of professionalism. Secondly, based on the recent UNESCO report on the "Futures of Education", it intends to discuss the dimension of the future as a key direction of meaning for educational policies and practices, held up as an alternative to anticipatory governance models (Robertson, 2022).